Szakértőt vagy politikust választanak a vajdasági magyarok? : elemzés a Magyar Nemzeti Tanács 2010-es évi megválasztásának folyamatáról - Pap, Tibor; Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2011)
It was only recently, in the early 2000’s, that the national councils were formed as institutions of policy making. The present paper concerns the second election of the national councils, which was held in the traditional way and not by means of electors. In 2010, the primary issue was whether and to what extent the institution is considered legitimate by majority of the Hungarians in Serbia. However, mitigating the collective social inequities of Hungarians in Serbia/Voivodina was not empha-sized. This inequity is partly due to the political deep structure of the representational form of rule. In other words, the dispute on the working of the MNT paralleled the current challenges of the Hungarian party-political system in Voivodina. The actual possibilities of minority policy making or the sensibly discussable circumstances of a given policy area were not really included. The discourse belonged to the dimension of politics rather than that of policies. Even the most skilled intellectuals were unaware of the ways how interests can be institutionalized through policy making. The debate addressed the elections of the MNT and not its procedures of functioning/competence/decision. The 2010 election facilitated the progress in the legality and legitimacy of the body but it also pointed out that, due to the short-term and tactical workings of daily political struggles, the political possibilities and articulations of minority interests will continue to be kept in the background.